An Analysis of the Presence and Composition of OutLists at United States, Canadian, and European Medical Institutions. Issue 14 (5th December 2020) - Zelin, Nicole Sitkin; Solotke, Michael T.; Scott, Caroline E.; Atienza-Carbonell, Beatriz; Fogas, Cristina; Skrzypczak, Jan; Starin, Rebeka; Tamburelli, Francesca; Ucar, Aykut; Pelzer, Benedikt W.
ABSTRACT: Sexual and gender minority (SGM) medical students and physicians are exposed to bias in professional contexts. One strategy for promoting SGM visibility and inclusion within medicine is the development of institutional OutLists, which are online, opt-in lists of SGM-identified individuals affiliated with an academic institution. We present the first quantitative evaluation of publicly accessible OutLists at medical institutions in the United States, Canada, and Europe. Nineteen OutLists were identified in the United States; no OutLists were identified in other countries. All OutLists in the United States were identified at allopathic institutions with no institutional religious affiliation. Clinicians in high-prestige specialties and more senior clinicians were underrepresented on OutLists. A state-level measure of SGM equality predicted presence of OutLists within the state (odds ratio 1.429, p = .047) but was not associated with the total number of individuals on OutLists. Future research would benefit from incorporating qualitative methodologies to explore the effectiveness of OutLists and the individual experiences of participants in these lists.